The Influence of Physical Training on The Flight Performance of Cadets - Fajar Islam; Muhammad Rosihan Aristo (Applied Quantitative Analysis, 2024)
This research was conducted to investigate the effect of physical exercise on the flight performance of fixed-wing cadets at Indonesia Civil Pilot Academy in Banyuwangi. The research employed a quantitative methodology, utilizing data collection through a questionnaire. The questionnaire was distributed to the cadets selected as samples, specifically DIII PST 2, DIII PST 3, and DIII PST 4 cadets, with 43 participants. Based on the instrument test conducted using regression analysis with ANOVA, it was found that the regression model (H1) significantly explained the variation in the observed data, with a significant F-ratio of 33.153 and a very low p-value (<.001). The hypothesis test results revealed that the coefficient for the dependent variable, flight performance, was 0.728, with a standard error of 0.126. The standardized coefficient (standardized) for this variable was 0.669. The obtained t-value was 5.758. The research findings indicate a significant influence of the independent variable, "physical exercise", on the dependent variable, flight performance. Aviation training facilities can use the results of this study to develop policies that encourage the inclusion of hands-on training in the flight curriculum. By doing this, you can ensure cadets are in good enough physical shape to complete their flight training. This study's results may open the door for the creation of fresh hypotheses on the connection between physical preparation and flying performance. The results of this study may serve as the foundation for creating a novel conceptual framework in this area.